Reliability of the Pinch Strength with Digitalized Pinch Dynamometer - Shin, Heesuk; Moon, Seung Won; Kim, Gab-Soon; Park, Jung Dong; Kim, Jin Hoan; Jung, Mi Jin; Yoon, Chul Ho; Lee, Eun Shin; Oh, Min-Kyun (Annals of rehabilitation medicine, 2012)
To examine the intra-rater, inter-rater, and inter-instrumental reliability of the digitalized pinch muscle strength dynamometer. Thirty normal subjects were examined for pinch strength, using both the Preston pinch gauge and the digitalized pinch dynamometer. The participants performed all pinch strength tests in the seated position as recommended by the American Society of Hand Therapists (ASHT). Three successive measurements were taken for each hand. The mean of the three trials was used for data analysis. The pinch strength tests performed used a repeated measure design and measurements were taken by each rater. The relationship between the Preston pinch gauge and the digitalized pinch dynamometer in pinch strength was reliable (the ICC were 0.821 and 0.785 in rater 1 and rater 2 respectively). The relationship between the first session and second session in pinch strength using the digitalized pinch dynamometer was reliable (the ICC were 0.872 and 0.886 in rater A and rater B respectively). The relationship between rater A and rater B in pinch strength using the digitalized pinch dynamometer was reliable (the ICC was 0.754). The pinch strength measurement using the digitalized pinch dynamometer is reliable within the rater and between raters. Thus, the Preston pinch gauge and the digitalized dynamometer measure grip strength equivalently, and can be used interchangeably.